Rapid Emergence and Clonal Dissemination of CTX-M-15–Producing Salmonella enterica Serotype Virchow, South Korea - Jin Seok Kim; Young-Sun Yun; Soo Jin Kim; Se-Eun Jeon; Deog-yong Lee; Gyung Tae Chung; Cheon-Kwon Yoo; Junyoung Kim (Emerging Infectious Diseases, 2016)
The prevalence of cefotaxime-resistant Salmonella enterica serotype Virchow has dramatically increased in South Korea since the first isolation in 2011. Of 68 isolates collected over 10 years, 28 cefotaxime-resistant isolates harbored the blaCTX-M-15 extended-spectrum β-lactamase gene and were closely related genetically, demonstrating the clonal dissemination of CTX-M-15–producing Salmonella Virchow in South Korea.